The United States and Military Coups in Turkey and Pakistan - Aslan, Ömer. author. aut Link
XV, 294 p. 6 illus. in color.
Keywords: This comparative study explores the involvement of the United States in four successful military coups in Turkey and Pakistan during the Cold War. Focusing on military-to-military relations with the US in each country, the book offers insight into how external actors can impact the outcomes of coups, particularly through socialization via military training, education, and international organizations such as NATO. Drawing upon recently declassified government documents and a trove of unexplored interviews with high-ranking officials, Ömer Aslan also examines how coup plotters in both countries approached the issue of US reaction before, during, and after their coups. As armed forces have continued to make and unmake Turkish and Pakistani governments well into the twenty-first century, this volume offers original, probing analysis of the circumstances which make coups possible.